The definition of "terrorist" under section 2 of the internal security act 1960 (act 82) is insufficient to combat modern forms of terrorism / Azalia Abdullah Abdul Aziz and Iza Dora Md Hanipah - Abdul Aziz, Azalia Abdullah; Md Hanipah, Iza Dora (2005)
This project paper intends to make recommendations on the improvements of the definitions of the word "terrorist" under Section 2 of the Internal Security Act 1960 (Act 82). This paper will concentrate more on the latest forms of terrorist acts which need to be included under the present definition of "terrorist" under the Internal Security Act 1960 (Act 82) (ISA). The paper will deal with the need for revised definitions on the word "terrorists" as under the Internal Security Act in order to make it more adequate to combat other forms of terrorism. There are many areas of the terrorist acts which are not included in the definition under the ISA, therefore there is a need for the improvement of the definition. This paper offers and advancement of knowledge to other possible forms of terrorism as terrorism is not only limited to what is mentioned under Section 2 of the Internal Security Act 1960 (Act 82).